Comparison of culture-dependent and culture-independent techniques in the detection of lactic acid bacteria biodiversity and dynamics throughout the ripening process: The case of Turkish artisanal Tulum cheese produced in the Anamur region - Demirci, Talha; Orac, Aysun; Aktas, Kubra; Dertli, Enes; Akyol, Ismail; Akin, Nihat (CAMBRIDGE UNIV PRESS, 2021)
Our objective was to analyze the diversity of the microbiota over 180 d of ripening of eight batches of artisanal goatskin Tulum cheeses by culture-dependent and culture-independent (PCR-DGGE) methods. V3 region of the bacterial 16S rRNA gene was amplified with the PCR after direct DNA isolation from the cheese samples. Nine different species and five genera were determined by culturing, while 11 species were identified in the PCR-DGGE technique. This diversity revealed the uniqueness of artisanal cheese varieties. The dominant genera in all the cheese samples were composed of Enterococcus species. The culture-dependent method revealed five genera (Enterococcus, Bacillus, Lactococcus, Lactobacillus, Sphingomonas) while three genera (Enterococcus, Streptococcus, Lactococcus) were detected in the culture-independent method. It was concluded that combining the two methods is important for characterizing the whole microbiota of the Tulum cheese varieties produced in the Anamur region.
Keywords: Artisanal; lactic acid bacteria; microbiota; ripening; Tulum cheese; MICROBIOLOGICAL CHARACTERIZATION; PCR-DGGE; DIVERSITY; RAW; MILK; Agriculture; Food Science & Technology